Pattern of Fingerprints in Relation to Blood Group and Gender - MUHAMMAD MAQSOOD, SYED HAMAD RASOOL, MUHAMMAD KHALID CHAUDHRY, MARIAM HAMAD (Journal of Fatima Jinnah Medical University, 2018)
Fingerprint is the one of the oldest, highly accurate and reliable biometric technologies. It is one of the best, cheapest and legitimate proofs of identification. A prospective study was conducted on 200 medical students(100 male & 100 female) belonging to age group 20-22 years at FMH College of Medicine & Dentistry, Lahore. This study showed that loops are the most commonly occurring fingerprint pattern while arches are the least common. Males have higher incidence of loops while females have higher incidence of whorls. Loops are predominant in Rh positive individuals of ABO blood group except in O positive subjects which showed higher frequency of whorls. Among Rh negative cases similar predominance of loops was seen in blood group O negative while whorls were most common in AB negative cases. Loops and arches were more frequent in Rh negative cases while whorls had highest incidence in Rh positive cases. This study suggests a relationship between distribution of fingerprint patterns, gender and blood group.